Biology and culture of Asian seabass Lates calcarifer - Jerry, Dean R. (CRC Press, 2014)
This book covers the biology, ecology, genetics and aquaculture of the Asian Seabass or barramundi (Lates calcarifer), a commercially and recreationally valuable species. It brings together in the one place reviews written by world experts in Asian seabass taxonomy, genetics, nutrition, ecology, aquaculture, reproductive and developmental biology, climate change impacts, harvest quality and health management.